2020
DOI: 10.3390/genes11111285
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Target of Rapamycin: A Conduc TOR of Nutrition and Metabolism in Photosynthetic Organisms

Abstract: Living organisms possess many mechanisms to sense nutrients and favorable conditions, which allow them to grow and develop. Photosynthetic organisms are very diverse, from green unicellular algae to multicellular flowering plants, but most of them are sessile and thus unable to escape from the biotic and abiotic stresses they experience. The Target of Rapamycin (TOR) signaling pathway is conserved in all eukaryotes and acts as a central regulatory hub between growth and extrinsic factors, such as nutrients or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 108 publications
1
31
0
Order By: Relevance
“…It is important to note that TOR is not exclusively activated by sugars. Readers are referred to Ingargiola et al (2020) for a detailed overview on the regulation of TOR [40]. By contrast, stresses like nutrient starvation, pathogen attack, and oxidative stress, often lead to sugar starvation in sink tissues.…”
Section: Sugar Signaling Translates Cellular Energy Statusmentioning
confidence: 99%
“…It is important to note that TOR is not exclusively activated by sugars. Readers are referred to Ingargiola et al (2020) for a detailed overview on the regulation of TOR [40]. By contrast, stresses like nutrient starvation, pathogen attack, and oxidative stress, often lead to sugar starvation in sink tissues.…”
Section: Sugar Signaling Translates Cellular Energy Statusmentioning
confidence: 99%
“…It is negatively regulated by the Target of Rapamycin (TOR) kinase, which, along with its effectors, is active under nutrient-rich conditions when it upregulates cell growth and translation, but it is inactive during nutrient deficiency. The TOR kinase complex is modulated by diverse upstream inputs to phosphorylate different proteins in the nucleus, nucleolus, and cytosol, thus controlling transcription, the cell cycle, rRNA transcription, ribosome biogenesis, translation, and metabolism, which are pivotal to cell proliferation and growth [ 131 , 132 ].…”
Section: Autophagy As a Cellular Degradation Pathway And A Part Of Intracellular Traffickingmentioning
confidence: 99%
“…In addition, the role of the TOR signaling plants' defense against pathogen and related metabolisms was studied recently [7]. When eukaryotes are in favorable conditions, TOR signaling pathway is active, which promotes anabolic processes and inhibits catabolism and protein degradation, but when conditions are unfavorable for growth, TOR is inactivated and promotes catabolic processes [8,9]. Xiong and Sheen explained the glucose-TOR signaling in the transcriptional control of the cell cycle and enumerated the importance of leaf photosynthesis-derived glucose in activating TOR [10].…”
Section: The Tor Complex In Plantsmentioning
confidence: 99%
“…In the model plant Arabidopsis thaliana, one copy of TOR gene, two copies of Raptor (RaptorA and RaptorB) genes, and two copies of LST8 (LST8-1 and LST8-2) genes exist [9,17]. Studies suggested that the null tor mutant is embryo-lethal, the raptora/b double mutant is unable to maintain post-embryonic meristem-driven growth, and the lst8-1 mutant exhibits modest dwarf growth and early senescence phenotypes [9,[34][35][36].…”
Section: The Tor Complex In Plantsmentioning
confidence: 99%